Transjugular Intrahepatic Portosystemic Shunt Reductions - Joseph, Arthur; Lopera, Jorge (Seminars in Interventional Radiology, 2023)
Transjugular intrahepatic portosystemic shunts (TIPS) are effective in reducing the portosystemic gradient and relieving complications of portal hypertension. Despite optimal patient selection, TIPS placement can be limited due to worsening hepatic encephalopathy and liver failure. In these cases, TIPS reduction may be necessary. A brief history of TIPS reduction and techniques for reduction are reviewed.
Keywords: interventional radiology; transjugular intrahepatic portosystemic shunt; portal hypertension; complication; hepatic encephalopathy